Aklatbp the new Antipolo City Public Library - Imperial, Julian Andrei A.; Ong, Simoun (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
The Philippines experienced promising growth in the recent years. If this continues, we may achieve our long term vision, which is "matatag, maginhawa at panatag na buhay". How then do we sustain the growth we enjoy and how do we make sure that everyone benefits from it? To reach its vision of having a globally-competitive knowledge economy, the plan states that one of the things that it should do is to enhance the social fabric by promoting Philippine culture and values through several means like liberalizing access to information on Filipino culture and expanding inclusive cultural structures as civic spaces for dialogue and cultural exchange like museums, cultural centers, and libraries. It was found out that the country has existing framework for public libraries. However, in comparison with other countries, such framework and standards are extremely inadequate. This is reflected in the low library visitation rates, significantly lower even compared to similarly developing countries. To answer this architecturally, the author attempts to design a public library that will act as the modern third place. The library is envisioned to transcend beyond its most basic function as a repository of knowledge, by providing spaces that will adapt to new means of acquiring knowledge, promote local culture, and advocate for participation and interaction in the community.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Public libraries -- Philippines; Public libraries -- Architectural Design -- Philippines